2019
DOI: 10.3390/jcm8060909
|View full text |Cite
|
Sign up to set email alerts
|

Facial Appearance and Psychosocial Features in Orthognathic Surgery: A FACE-Q- and 3D Facial Image-Based Comparative Study of Patient-, Clinician-, and Lay-Observer-Reported Outcomes

Abstract: Outcome measures reported by patients, clinicians, and lay-observers can help to tailor treatment plans to meet patients’ needs. This study evaluated orthognathic surgery (OGS) outcomes using pre- and post-OGS patients’ (n = 84) FACE-Q reports, and a three-dimensional facial photograph-based panel assessment of facial appearance and psychosocial parameters, with 96 blinded layperson and orthodontic and surgical professional raters, and verified whether there were correlations between these outcome measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The orthodontic-surgical technical details (virtual planning, modified surgery-first approach, single splint technique, two-jaw surgery and genioplasty, and with no postoperative intermaxillary immobilization) adopted in this study have been beneficial not only for correction of the occlusal function, but also to achieve facial symmetry, balance, proportion, and improved aesthetics in successive cohorts of skeletofacial surgery-treated patients at our center in recent years 11,12,2940 . For the particular planning and execution of facial asymmetry correction, 3D simulation helps to demonstrate the rotation of both proximal and distal ramus segments with maintenance of intersegmental space and angulation between proximal and distal segments to achieve the desired facial symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The orthodontic-surgical technical details (virtual planning, modified surgery-first approach, single splint technique, two-jaw surgery and genioplasty, and with no postoperative intermaxillary immobilization) adopted in this study have been beneficial not only for correction of the occlusal function, but also to achieve facial symmetry, balance, proportion, and improved aesthetics in successive cohorts of skeletofacial surgery-treated patients at our center in recent years 11,12,2940 . For the particular planning and execution of facial asymmetry correction, 3D simulation helps to demonstrate the rotation of both proximal and distal ramus segments with maintenance of intersegmental space and angulation between proximal and distal segments to achieve the desired facial symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be possible that the presence of poor or the lack of significance for the tested correlations may not be associated to the incapacity of each tool to detect relevant features from the patient (nose and nostril appearance) and the abnormalities (clefts versus dentofacial deformities versus normal individuals). Studies have reported that the appraisal of correlations between two different outcome measurement tools has implications for the ongoing discussions regarding the correct interpretation and application of each existing tool in clinical and research settings 18,39,40 . Therefore, further investigation is important to improve our understanding of the assessed tools by testing further predefined hypotheses about expected correlations, as it would attenuate the risk of bias and assist researches to avoid substitute justifications after data analysis, as defined before our data collection.…”
Section: Discussionmentioning
confidence: 99%
“…We also verified the subjective perceptions from blinded raters using the panel assessment, an outcome measure tool frequently embraced in OGS literature 49 . Interestingly, the post-OGS panel assessment-based results revealed that raters appraised the patients treated with 3D simulation as more symmetrical than 2D planning-treated patients, proposing that the facial changes after OGS treatment impacted the raters' perceptions.…”
Section: Lateral Lower Chin N (%)mentioning
confidence: 99%